African Cotton Markets at Crossroads : Will the Price Spike Turn into a New Kick-Start? - Delpeuch, Claire (2012)
After years of diplomatic efforts and legal procedures to obtain the elimination of rich countries' cotton subsidies, policy prospects for African cotton producers remain bleak. However, the world price for cotton has doubled in a year and has hit an all-time high. This paper examines these developments and investigates their potential consequences for African smallholder farmers. It emphasizes the importance of price transmission to domestic markets; assesses the impact of the reforms undertaken in Sub-Saharan African cotton sectors on producers' supply responsiveness; and outlines what remains to be done to ensure that farmers can benefit from a favorable global environment. The paper concludes that improving the functioning of domestic markets remains the priority in the short run. The current high price season will reveal the costs and benefits of different types of sector regulation systems and the capacity of policy-makers and sector stakeholders to deliver on promises. It also offers a last-minute opportunity to rich countries to keep their word in the context of the Doha Development Round.